Evaluación del desempeño de las variables del comportamiento organizacional a nivel organizacional en la pasteurizadora y comercializadora El Ranchito, del cantón Salcedo - Montesdeoca Cedeño, Jhonatan Ramón (2016)
The aim of this research was to evaluate the variables performance of Organizational Behavior at the organizational level in the pasteurizer and marketer El Ranchito, at the Salcedo Canton. Four methodological stages were structured to carry out the research; the selection of variables, the design of the assessment tool, its implementation and the improvement plan. In the first phase, the company was characterized, and using the method of coefficient competence, a group of experts were chosen who selected the correct variables to be evaluated in the research. In the second phase, it was selected and designed the assessment tool identifying key indicators as bibliographic consultations that enable to measure the performance of the variables under study. In the third phase, analysis and statistical processing of the information obtained were performed by applying the evaluation tools. With the variables that showed greater weaknesses, a proposal for an improvement plan in order to contribute to the solution of problems that strongly affect on organizational behavior. It was concluded that motivation and organizational climate in the pasteurizer and marketer El Ranchito provided with a good score of 78% and 83% respectively. Whereas the main problems found were that the company does not provide with plenty of opportunities for economic or professional growth for its workers and there is lack of mutual cooperation and teamwork at the time of performing the given responsibilities.